Paciente de sexo masculino de 72 años con insuficiencia respiratoria aguda. - Moran Proaño, Iván Ismael (2021)
Acute respiratory failure (ARF) is not a pathology in itself, but the effect of a sequence of inconveniencies that interfere with the respiratory system´s ability to properly consume its important function, which is ingesting O2. Acute respiratory distress syndrome usually occurs in people who are already seriously ill or have significant injuries. The mechanical cause of acute respiratory distress syndrome is fluid leaking from the smaller blood vessels in the lungs into the tiny air sacs where the blood is oxygenated. Normally, a protective membrane keeps the fluid in the blood vessels. However, serious illness or injury can cause damage to the membrane, leading to fluid leakage from the acute respiratory difficulty syndrome. To diagnose acute respiratory failure, your doctor will do a physical exam and ask you about your medical history and symptoms. The doctor should also ask about bad habits, drug use, and ask about a personal history of asthma, chronic obstructive pulmonary disease (copd). Heart disease, neuromuscular diseases, restrictive practices, etc.